2019
DOI: 10.15305/ijrci/v7i1/316
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of drug use and factors affecting adherence to medication in patients with rheumatoid arthritis: A prospective, observational, hospital- based study

Abstract: Adherence to medication is explained as a strong thought for the need of the medicine. 6 The adherence to drug therapy can significantly improve the efficacy of the treatment regimen and lower healthcare cost. The adherence reported in RA patients ranges from 30-80%. 7 Data from Indian studies report non-adherence/noncompliance to antirheumatic drugs among 52% of the patients, and interrupted compliance among 6%. 2 Sharma et al. (2015) reported dissatisfaction to drug therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Among all patients, 70 were females, and 5 were males. A similar finding was reported by Sripreethy etal, 2 Moreland et al, 8 Nakagava et al, 10 Marras et al, 11 Bharthi etal, 12 Sharma et al, 18 van den Bemt et al 23 Refer Table 1 for the detailed demographic characteristics of the patients.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Among all patients, 70 were females, and 5 were males. A similar finding was reported by Sripreethy etal, 2 Moreland et al, 8 Nakagava et al, 10 Marras et al, 11 Bharthi etal, 12 Sharma et al, 18 van den Bemt et al 23 Refer Table 1 for the detailed demographic characteristics of the patients.…”
Section: Resultssupporting
confidence: 80%
“…This finding was in accordance in the systematic review published by Annalieke et al 14 Other studies carried out with a similar objective also reported similar findings. 23,24 In contrast to this, study conducted by Bharthi et al 12 and Wabe et al 17 showed improvement in adherence with increasing age. The level of education also did not correlate with the adherence to drugs, indicating that even highly educated individuals may have less than satisfactory drug compliance.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30][31] Likewise, it has been determined that the number of studies examining the treatment adherence levels of rheumatoid arthritis patients is high. [32][33][34][35][36][37][38][39][40][41] However, it has been determined that the number of studies on the continuity of care in rheumatoid arthritis patients is limited to only one study, 42 and more importantly, there is no study that evaluates the relationship between continuity of care and health outcomes with a comprehensive disease management approach.…”
Section: Introductionmentioning
confidence: 99%
“…When the literature on rheumatoid arthritis is examined, it is possible to come across studies that examine the effects of rheumatoid arthritis on health outcomes such as quality of life and physical activity disorder in terms of one dimension in both international and national literatüre 22–31 . Likewise, it has been determined that the number of studies examining the treatment adherence levels of rheumatoid arthritis patients is high 32–41 . However, it has been determined that the number of studies on the continuity of care in rheumatoid arthritis patients is limited to only one study, 42 and more importantly, there is no study that evaluates the relationship between continuity of care and health outcomes with a comprehensive disease management approach.…”
Section: Introductionmentioning
confidence: 99%